Acute‐on‐Chronic Liver Failure: An Old Entity in Search of Clarity. Issue 12 (10th December 2018) - Garcia‐Tsao, Guadalupe
Abstract : It is a commentary intended to outline and try to clarify some of the issues that have led to confusion in the field regarding acute‐on‐chronic liver failure.